Concentration‐dependent linkage of dietary methionine restriction to the components of its metabolic phenotype. Issue 4 (6th March 2017) - Forney, Laura A.; Wanders, Desiree; Stone, Kirsten P.; Pierse, Alicia; Gettys, Thomas W.
Abstract : Objective: Restricting dietary methionine to 0.17% produces a series of physiological responses through coordinated transcriptional effects in liver and adipose tissue. The goal of the present work was to determine the threshold concentrations above and below 0.17% at which the beneficial responses to 0.17% dietary methionine are preserved. Methods: Diets were formulated to restrict methionine to different degrees, followed by evaluation of the transcriptional and physiological responses to the different diets. Results: Restriction of dietary methionine to 0.25%, but not 0.34%, was partially effective in reproducing the metabolic phenotype produced by restriction of methionine to 0.17%, while restriction of methionine to 0.12% reproduced the responses produced by restriction to 0.17% but failed to support growth and caused excessive weight loss. Restriction beyond 0.12% initiated responses characteristic of essential amino acid deprivation including food aversion and rapid weight loss. Conclusions: Restriction of dietary methionine to levels above 0.25% was without effect, while restriction to levels below 0.12% produced responses characteristic of essential amino acid deprivation. In addition, although restriction of dietary methionine to 0.12% did not evoke essential amino acid deprivation responses, it provided insufficient methionine to support growth. The ideal range of dietary methionine restriction was from 0.17% to 0.25%.